Laboratory Leaching Tests to Investigate Mobilisation and Recovery of Metals from Geothermal Reservoirs - Máté Osvald; Andrew D. Kilpatrick; Christopher A. Rochelle; János Szanyi; Tamás Medgyes; Balázs Kóbor (Geofluids)
The H2020 project “Combined Heat, Power and Metal extraction” (CHPM2030) aims at developing a novel technology which combines geothermal energy utilisation with the extraction of metals in a single interlinked process. In order to improve the economics of geothermal-based energy production, the project investigates possible technologies for the exploitation of metal-bearing geological formations with geothermal potential at depths of 3–4 km or deeper. In this way, the coproduction of energy and metals would be possible and could be optimized according to market demands in the future. This technology could allow the mining of deep ore bodies, particularly for critical metals, alongside power production, while minimizing environmental impact and costs. In this paper, we describe laboratory leaching experiments aimed at quantifying the relative rates and magnitudes of metal release and seeing how these vary with different fluids. Specific size fractions (250–500 μm) of ground mineralised rock samples were investigated under various pressures and temperatures up to 250 bar and 250°C. Initial experiments involved testing a variety of potential leaching fluids with various mineralised samples for a relatively long time (up to 720 h) in batch reactors in order to assess leaching effectiveness. Selected fluids were used in a flow-through reactor with shorter contact time (0.6 h). To ensure possible application in a real geothermal reservoir, a range of fluids were considered, from dilute mineral acid to relatively environmentally benign fluids, such as deionised water and acetic acid. The main findings of the study include fast reaction time, meaning that steady-state fluid compositions were reached in the first few hours of reaction and enhanced mobilisation of Ca, Cd, Mn, Pb, S, Si, and Zn. Some critical elements, such as Co, Sr, and W, were also found in notable concentrations during fluid-rock interactions. However, the amount of these useful elements released is much less compared to the common elements found, which include Al, Ca, Fe, K, Mg, Mn, Na, Pb, S, Si, and Zn. Even though concentrations of dissolved metals increased during the tests, some remained low, and this may present technical challenges for metal extraction. Future efforts will work toward attaining actual fluids from depth to more tightly constrain the effect of parameters such as salinity, which will also influence metal solubility.